(untitled) (Research, Society and Development, 2021)
Objective: The aim of this study was to evaluate in vitro the bond strength through the microtensile test of flow-type bulk fill composite resins to the dentin of the cervical margin of class II cavities of newly extracted human molars. Methodology: Fifty cavities 4 mm deep and 3 mm wide buccolingually, mesial and distal, of 25 molars were standardized. The cavities (n=10) were restored with the following resins: Filtek Z350XT and Filtek Flow (3M/ESPE); Filtek Bulk Fill Flow (3M/ESPE); Surefill SDR Flow (Dentsply) and X-tra Base (Voco). After 24 hours in an oven (37ºC), the samples were sectioned on sticks from the cervical wall of the proximal boxes, with an area and cross section of ± 1mm2 and pulled in a universal testing machine (Kratos/model IKCL3-USB), speed of 1mm /min. Data obtained in MPa were submitted to ANOVA and Tukey statistical tests (p<0.005). The mean of the highest bond strength was recorded in the SDR group (64.37 MPa), followed by the X-tra Base (41.46 MPa), Filtek Flow (36.85 MPa), Filtek Bulk Fill Flow (26.98Mpa) and Filtek Z350 (20.99 MPa) groups. MPa). Conclusion: The low viscosity bulk fill resins studied showed satisfactory bond strengths on the cervical walls of class II cavities.